Beyond and Against White Settler Colonialism in Palestine: Fugitive Futurities in Amir Nizar Zuabi's "The Underground Ghetto City of Gaza". (February 2017) - Ritskes, Eric
This article theorizes the fugitive futurities of decolonization, seeking futures beyond colonial constructions of the possible and the sensible. To do this, I engage with a close reading of Palestinian writer Amir Nizar Zuabi's short story, "The Underground City of Gaza, " as an example of a fugitive trajectory that refuses inclusion into the colonial state through recognition, instead, re-centering modes of fugitive flight within the land itself—highlighting the necessary interplay between the re-routing and re-rooting of decolonization. In doing so, Zuabi demonstrates how decolonial futures evacuate colonial definitions of humanity, as well as colonial relationships with land and body that are based on property ownership. Working from Indigenous and radical Black theorization of land and fugitivity, my theorizing of fugitive futurity learns from Zuabi's centering of land in imagining routes of flight, demonstrating how epistemologies of land both challenge colonial relations and also resurge alternative futures; re-rooting decolonial struggle in the land is also an act of re-routing toward decolonial futures.